The Influence of STEAM-Based Learning Application on Students' Critical Thinking Ability - Syukri, Muhammad; Ukhaira, Zhaifatul; zainuddin, zainuddin; Herliana, Fitria; Arsad, Nurazidawati Mohamad (Universitas Syiah Kuala, 2022)
The learning process in Indonesia has not directed students to be able to think at a high level which resulted in the quality of education in Indonesia is still quite low. This study aims to determine the effect of the application of STEAM-based learning on students' critical thinking skills. This research is a